Effect of heat treatment on the microstructure and mechanical properties of laser power bed fusion AlSi10Mg - Li, Kairui (Nanyang Technological University, 2024)
This study examines how the microstructure and mechanical properties of the Laser Power Bed Fusion (LPBF) AlSi10Mg alloy are affected by heat treatment parameters such as cooling methods, solution treatment temperatures, and aging times. The rapid solidification intrinsic to the LPBF process leads to a refined microstructure with much higher hardness and strength than those of the alloy fabricated using the conventional manufacturing (CM) method. The goal is to modify the microstructure of the LPBF AlSi10Mg to match that of CM AlSi10Mg, while enhancing its mechanical properties. According to the results, faster cooling methods improve grain refinement and hardness, solution treatment homogenizes the microstructure and aging first increases the hardness but eventually reduces strength. By adjusting these variables, a desired balance of mechanical properties can be obtained, indicating that LPBF AlSi10Mg has the potential to be a competitive substitute for conventionally manufactured alloy